HEART AND AGE (PART II): CLINICAL MANIFESTATIONS OF AGEING - D. U. Akasheva; E. V. Plokhova; I. D. Strazhesko; E. N. Dudinskaya; O. N. Tkacheva (Кардиоваскулярная терапия и профилактика, 2013)
Ageing is an inevitable process which affects quality of life and reduces life expectancy. Age-related cardiac changes reduce compensatory reserves of the heart and accelerate the disease development. Such changes in cardiac structure and function, observed in the absence of cardiovascular disease (CVD), are considered age-related. However, taking into account the high prevalence of CVD in the elderly, it is problematic to define the genuine cardiac ageing. This review discusses a range of subclinical cardiac conditions which are common in older people.